2020
DOI: 10.1002/ehf2.12939
|View full text |Cite
|
Sign up to set email alerts
|

Association between base excess and mortality in patients with congestive heart failure

Abstract: Aims The relationship between baseline base excess (BE) and survival outcomes in patients with congestive heart failure (CHF) is unclear. Therefore, we aimed to investigate this relationship based on the Multiparameter Intelligent Monitoring in Intensive Care III (MIMIC-III) database (v1.4). Methods and results This retrospective cohort study included 5956 adult patients with CHF from the MIMIC-III database from 2001 to 2012. Using the Cox proportional-hazard analysis and Kaplan-Meier plot, we evaluated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In the multivariable RCS model, a positive linear relationship was observed. Another study also showed a U-shaped association between BE and survival outcomes among patients with congestive heart failure ( 3 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the multivariable RCS model, a positive linear relationship was observed. Another study also showed a U-shaped association between BE and survival outcomes among patients with congestive heart failure ( 3 ).…”
Section: Discussionmentioning
confidence: 95%
“…Base excess has been widely used as a predictor for the diagnosis of neonatal sepsis in pre-term newborns (5), complications in cytoreductive surgery (6), or the prognosis of neonatal acute respiratory distress syndrome (7). The indicator also shows significant representativeness in heart failure (3,4). However, the association between BE and mortality among patients with AKI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Base excess has been widely used as a predictor for diagnosis of neonatal sepsis in preterm newborns 5 , complications in cytoreductive surgery 6 , or the outcome of neonatal acute respiratory distress syndrome 7 . The indicator also shows signi cant representativeness in heart failure 3,4 . However, the association of BE and mortality of patients with AKI is unclear.…”
Section: Introductionmentioning
confidence: 86%
“…Base excess (BE) refers to the amount of acid or alkali needed to adjust the value to the normal range 3 , which is considered as a pure indicator of metabolic acid-based balance 4 . Base excess has been widely used as a predictor for diagnosis of neonatal sepsis in preterm newborns 5 , complications in cytoreductive surgery 6 , or the outcome of neonatal acute respiratory distress syndrome 7 .…”
Section: Introductionmentioning
confidence: 99%